24 Reducing harm in chest drains: transforming culture and implementing change. (31st October 2017) - Belton, Moerida; Hickman, Sally; Attree, Anita; Collier-Keywood, Joshua; Dunwoody, Roisin
Abstract : Aims: To improve the safety and quality of care provided to patients with chest drains. Background: Between Oct 2013 and June 2014 a series of serious clinical incidents (SI) including a "Never" event occurred within our Trust. We identified deficiencies in formal teaching and assessment of competency existed within the Trust. We found that standards of care and documentation varied greatly and that the existing Trust policy was out dated. Methods: We undertook a review of all SI's occurring during this period to identify common themes. Subsequently, an Aspiring to Excellence in Chest Drains (A2E) cross-disciplinary working group was convened. Our approach to improving standards of care and safety was multifaceted. In order to improve safety and training, we developed a new dedicated monthly chest drain study day for all nurses and doctors. A new Trust policy and Integrated Chest Drain Care bundle were introduced with specific emphasis on the role and responsibility of doctors and nurses. In order to ensure safe and sterile techniques, we designed, built and commissioned a dedicated pleural procedures room with ultrasound facilities. Results: An audit of chest drains comparing standards of care before and after the introduction of the interventions demonstrated a dramatic improvement. We achieved a significant improvement in nursing documentation (45% vs 100% post introduction). The use of ultrasound increased to 100% of chest drains following the intervention (prior 81%). Levels of supervision increased and no junior doctor was found to undertake unsupervised procedures. Finally, all chest drain patients were shown to be cared for in the correct clinical area with trained and competent staff. Conclusion: A multifaceted, cross-specialty approach to improving chest drain care has resulted in a dramatic improvement in standards of care for these patients.